أثر القرارات المالية على القيمة السوقسة للمؤسسة الاقتصادية /دراسة حالة مؤسسة مسعرة ببورصة الجزائر خلال الفترة 2013-2016 - نور الإيمان رحاحلي; محمد صلاح نوري (My University, 2021)
This study aims to highlight the impact of financial decisions on the value of the economic institution, and try to drop this issue on the Saidal complex, by studying and analyzing its financial statements during the period from 2013 to 2016, using some financial analysis tools such as the rate of return on investment, financial profitability , and economic profitability, and this is with regard to the investment decision variables, as well as when we study the variables of the dividend decision, which are (DPA - PBA - RPA) and the financing decision variables. (D - DL - DC) This is in order to identify the various concepts related to the value of the institution, with a focus on the various methods of evaluation, and to try to research the impact of financial decisions on the market value of the institutions listed on the Algiers Stock Exchange, especially the Saidal Complex, which is the subject of the study. Where the study concluded that the financial decisions (dividend distribution decision, investment decision, financing decision) are among the most important elements in the institution, as on the basis of which the future of the Saidal complex is determined. ........................................................... تهدف هذه الدراسة إلى إبراز تأثير القرارات المالية على قيمة المؤسسة الاقتصادية، ومحاولة إسقاط هذا الموضوع على مجمع صيدال، من خلال دراسة وتحليل قوائمها المالية خلال الفترة الممتدة من سنة 3102 إلى سنة 3102 ، باستخدام بعض أدوات التحليل المالي مثل معدل العائد على الاستثمار، المردودية المالية، والمردودية الاقتصادية، وهذا بالنسبة لمتغيرات قرار الاستثمار وكذلك عند دراستنا لمتغيرات قرار توزيع الأرباح وهي ) DPA – PBA RPA ( ومتغيرات قرار التمويل (D – DL – DC) وهذا من أجل التعرف على مختلف المفاهيم المرتبطة بقيمة المؤسسة مع التركيز على مختلف طرق التقييم ، ومحاولة البحث في مدى تأثير القرارات المالية على القيمة السوقية للمؤسسات المسعرة في بورصة الجزائر ، خاصة مجمع صيدال الذي هو محل الدراسة . حيث خلصت الدراسة بان القرارات المالية ) قرار توزيع الأرباح ، ق رار الاستثمار ، قرار التمويل ( من أهم العناصر في المؤسسة إذ على أساسها يتحدد مستقبل مجمع صيدال .